Pseudomiopía en paciente femenino de 31 años. - Franco Uriarte, Washington Leonardo (2023)
Pseudo myopia is caused by an excess of accommodation and is generated by bad visual habits or excessive work in near vision. Its main symptoms are asthenopia, headache, blurred vision, difficulty changing vision from near to far, these appear after long working time. In the present case we have a 31-year-old female patient, a teacher in the computer area, who presents for consultation due to visual acuity problems. Objective: to identify the causes of pseudo myopia in a 31-year-old female patient, theoretically supporting the diagnosis of this clinical case. Method: The deductive and inductive method was applied, analyzing the data from the tests performed on the patient. Result: the exams reveal normal eye movements, presenting pseudo myopia due to accommodative excess. Conclusions: when a person presents problems in visual acuity, it is necessary to carry out the pertinent tests to rule out this type of problem, pseudo myopia can be treated through visual therapy and it is necessary for patients to acquire visual health care practices. The shortcomings in visual acuity are caused by the excessive use of electronic equipment. Visual therapy and rest are recommended.